Strengthening sustainable real estate management through citizen participation - Mejía Gómez, Gabriela (Street Art & Urban Creativity, 2025)
The growth of the city foresees that sustainable development and urban governance is important to identify urban actors framed in citizen participation processes. The public-private sector as promoters in the construction of the territory have maintained a biased vision towards the inclusion of social actors, without making visible the multiple enriching criteria for urban regeneration. This article is part of a doctoral research, focusing its Hypothesis on new real estate management models that involve citizen participation. The methodology is based on the systematic review of scientific literature and the qualitative analysis of indicators that make visible actions to strengthen real estate management towards sustainable development. The results show the importance of cooperation processes with indicators and actions that strengthen public-private collaboration. It is concluded that citizen participation contributes to sustainable development by strengthening urban and real estate management processes as an opportunity for participatory design in the territory.